PERLINDUNGAN HUKUM BAGI SUBJEK PENELITIAN KESEHATAN DITINJAU DARI ETIKA DAN TANGGUNG JAWAB - Lalu Mariawan Alfarizi; Novita Listyaningrum (STIS Darussalam Bermi, 2024)
Legal protection is everyone's right, including legal protection for research subjects. This research includes observational and experimental research. In these two types of research, students need to involve research subjects, both experimental animals and humans. In its implementation, it is necessary to obtain permission to be involved as a research subject in health research. This relates to fulfilling the rights and legal protection of health research subjects, especially in the field of dental education. This research is sociological juridical research, with analytical descriptive research specifications. This research uses sources from primary data and secondary data with data collection methods through field studies and literature studies to obtain the required data. The analysis method uses qualitative data analysis. Legal protection, both preventive and repressive, for health research subjects has not been realized even though there are legal provisions that regulate it, so firmness is needed in the implementation process.